Water Quality Impact on Flotation Response: A Focus on Specific Ions and Temperature - Charamba, Apollonia Anesu (Department of Chemical Engineering, 2023)
Factors such as water scarcity and environmental restrictions have brought about the need to recycle process water within the mining industry. This recycling however causes an accumulation of ions in the process water which may affect plant processes since processing routes are water-intensive. Seasonal temperature differences affect the water quality through variation of the available recycled water within the plant between the summer and winter seasons. Literature highlights that flotation efficacy is reliant on the differences in mineral surface properties. Chemical reagents are used to increase the separation of valuable mineral (which is usually hydrophobic) from unwanted gangue (which is usually hydrophilic). Literature also highlights that different ores and different minerals react differently to temperature variation. The presence of certain species in process water with water variation has been seen to impact the flotation response. It stands to reason that simultaneously varying the temperature and specific ions concentrations will affect the interaction of minerals and reagents thus affecting the flotation response of target minerals. This is a temperature-controlled flotation chemistry study that adopted a three-level-four-factor (3 4 ) factorial experimental design to evaluate the simultaneous effects of temperature and specific ions; Ca2+, SO4 2- and S2O3 2- as well as determined the possible interactive effects between the chosen parameters. A low-grade copper-nickel platinum group element (Cu-Ni-PGE) ore from the Kevitsa Igneous Complex in Lapland, Finland was floated in a complex water matrix that mimics onsite process water. This ore is remarkably similar to the Merensky ore in South Africa, meaning that the results of this study may apply to the South African mining industry. Sequential batch flotation tests were conducted, targeting copper flotation with Aerophine 318A as the copper collector. Consequently, followed by targeting nickel flotation with sodium isopropyl xanthate (SIPX) used as the respective collector. Carboxymethylcellulose (CMC) was the depressant used and Nasfroth 240 was the frother used. The objective of this study was therefore to investigate the effect of specific ions and temperature, relevant to onsite process water recycling and temperature variations brought about by seasonal changes, on the separation of gangue from valuable minerals in batch flotation of a low-grade Cu-Ni-PGE ore. The study demonstrated that there are specific ion concentration ranges beyond which flotation performance was adversely affected and other ranges beyond which no observable effect on flotation was visible. Based on this understanding, it may be possible to predict the ideal operating conditions for the number of water recycles in a plant. The effects of single variables and the interactions between variables were reflected in some responses. The higher ionic concentrations and their corresponding ionic strengths resulted in a more stable froth in comparison to lower ionic concentrations and consequently an improvement in the recoveries. Water and solids recoveries were impacted by the interaction of Ca2+ and SO4 2- . At high SO4 2- concentration an increase in Ca2+ increased the mass of water and solids recovered. An increase in SO4 2- alone caused an increase in copper recovery whilst decreasing the copper grade. S2O3 2- alone affected the nickel recovery. An increase in S2O3 2- caused an increase in nickel recovery whilst the nickel grade was affected by the interaction of S2O3 2- and temperature. Furthermore, copper showed similar trends as those observed for nickel in the responses for the mineral grade. At high S2O3 2- concentration there was no observable change in the nickel and copper grades when temperature increased. At low S2O3 2- concentration, an increase in temperature decreased the nickel and copper grades. In addition to the interactive effect of temperature and S2O3 2- , nickel was more temperature sensitive in comparison to copper. It may thus be concluded that the postulated hypotheses are supported by this work.